Self-treatment using 0.25%-0.50% podophyllotoxin-ethanol solutions against penile condylomata acuminata: a placebo-controlled comparative study. Issue 2 (April 1994) - von Krogh, G; Szpak, E; Andersson, M; Bergelin, I
Abstract : OBJECTIVE--To compare the efficacy of 0.50% and 0.25% podophyllotoxin preparations against previously untreated penile warts. DESIGN--The study was performed as a double-blind, placebo-controlled investigation on 57 males randomly allocated to one of three groups of 19 males in each, receiving either the placebo solution (70% ethanolic vehicle) or one of the two podophyllotoxin preparations for 1-2 self-treatment courses b.i.d. for three days, separated by a one-week drug-free interval. SETTING--The STD out-patient clinic of the Department of Dermatovenereology at Southern Hospital of Stockholm, Sweden. RESULT--The placebo solution merely exerted a marginal influence on the warts while a primary cure was documented in 72% (13/18) and 81% (13/16) of altogether 34 evaluable men who treated their warts with 0.25% and 0.50% podophyllotoxin, respectively. Follow-up investigation (range 5-23 weeks) was possible for 24 of 26 podophyllotoxin treated men who were primarily cured. Some degree of relapse occurred in nine of them (38%). Of these relapses, warts occurred on previously untreated sites only in three cases (33%), and in another four (44%) relapse was associated with regrowth on treated sites as well as on new sites. When analysing the debulking potential of podophyllotoxin, it appeared that 0.25% podophyllotoxin eradicated 184 of originally 217 warts (85%); the corresponding figure for 0.50% podophyllotoxin was as high as 130 of 135 lesions (96%). Side effects were generally mild-moderate and well tolerated. CONCLUSION--The results underscore the potential usefulness of low-dose podophyllotoxin preparations as first-line chemotherapy of condylomata acuminata for home-treatment. The efficacy from topical use of 0.25% podophyllotoxin detected in the study is certainly of a magnitude signifying that podophyllotoxin concentrations lower than 0.50% deserve further investigation if the drug may be incorporated into alternative vehicles such as creams or ointments.